Slum clearance : the social and administrative context in England and Wales - English, John, 1944-; Madigan, Ruth, active 1976; Norman, Peter, active 1976 (Routledge library editions. Urban studies, 2017)
Slum clearance is a particularly significant process because it places the ordinary citizen in a state of extreme dependence on his local authority. The local authority not only destroys his existing environment but controls access to a replacement council house. This book highlights both the control over the life chances of individual citizens which local government can exercise and the potential impotence of citizens caught up in a complex bureaucratic process. It investigates the difficulties faced by individuals in exercising even the rights and choices which are ostensibly provided by the existing structure. The book also seeks to apply theories of urban sociology in exploring the control of access to public housing. The essential objective of this study is demystification of the administrative processes of slum clearance and rehousing through analysis of local authority bureaucracy and its impact on individuals.